Exploring Students’ Motivation in Learning Arabic Speaking Skills: A McClellandian Perspective from an Islamic Boarding University - Gautama Veri Vetiana; Rohmanudin Rohmanudin; Fadhilah Samhabib; Laili Mas Ulliyah Hasan; Moh. Buny Andaru Bahy; Umma Fatayati (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
Motivation plays a crucial role in fostering learners’ success in acquiring Arabic speaking skills, particularly within immersive language environments. However, limited studies have examined Arabic speaking motivation through McClelland’s theory of needs in Islamic higher education contexts. This study aims to explore the motivational dynamics underlying students’ engagement in learning mahārah al-kalām within the matriculation program at Darussalam Gontor University. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and document analysis involving matriculation students and instructors. The findings reveal that students’ motivation is shaped by three interrelated needs proposed by McClelland: achievement, affiliation, and power. Achievement needs are reflected in students’ efforts to improve speaking performance and attain academic excellence. Affiliation needs emerge through intensive social interactions in the boarding-school environment, which encourage consistent Arabic language use. Meanwhile, power needs are manifested in students’ aspirations to influence peers, lead discussions, and demonstrate communicative competence. The study further highlights the significant role of the boarding-based language environment in strengthening these motivational dimensions and sustaining speaking practice. The findings contribute to the theoretical development of motivation studies in Arabic language learning and offer practical implications for designing language-environment-based speaking programs in Islamic higher education institutions.